ASPECTS OF THE STATE OF BIBLIOTHERAPY IN BELGIUM AND FRANCEA RESEARCH PROJECT - Genova, Teodora (E-Journal VFU, 2025)
This acticle presents a scientific study on the state of bibliotherapy in two European countries - Belgium and France, about which very little is known in Bulgaria. The research involved 4 organizations from both countries, which give representative answers about the extent of the use of bibliotherapy in their practical work and project activities. Research data were obtained through online questionnaires, video calls, online correspondence and on-site interviewing. The purpose of the presented data is to outline more clearly the state of the field of bibliotherapy and to borrow good practices in the use of bibliotherapy methods when working with different target groups. The results of the research would serve both specialists in the field of bibliotherapy in Bulgaria and people who are engaged in bibliotherapy in both countries, since there is a lack of sufficiently organized information about the development of the field among the specialists themselves in the countries under consideration.